Catalyst layer

By using a carrier with a small specific surface area and a high aspect ratio conductive additive in the fuel cell catalyst layer, the problems of oxidation deterioration and densification of carbon support are solved, and a catalyst layer with low gas diffusion resistance and proton resistance are realized, which improves the Performance of fuel cell.

CN114628703BActive Publication Date: 2025-01-07TOYOTA JIDOSHA KK
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202111512180.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-12-10
Filing Date
2021-12-07
Publication Date
2025-01-07
Estimated Expiration
2041-12-07

AI Technical Summary

Technical Problem

In fuel cells, deterioration of oxidation of high crystalline carbon support leads to a decrease in dynamic performance, and when a carbon support with a smaller specific surface area is used, densification of the catalyst layer leads to an increase in gas diffusion and proton resistance, affecting power generation performance.

Method used

A carrier with a smaller specific surface area is used to mix with a conductive additive with a high aspect ratio of unsupported catalyst metal. The proportion of the conductive additive is between 2-20 mass%, and no hydrophilization is performed to form a low gas diffusion resistance. and catalyst layer of proton resistance.

Benefits of technology

The initial power generation performance and durability of the fuel cell are improved, the gas diffusion resistance and proton resistance are reduced, and the hydrophobicity and void ratio of the catalyst layer are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003396233190000101
    Figure BDA0003396233190000101
Patent Text Reader

Abstract

The present invention provides a catalyst layer having low gas diffusion resistance and low proton resistance even when a carrier with a small specific surface area is used. The catalyst layer for a fuel cell is characterized in that the catalyst layer comprises a catalyst metal, a carrier and a conductive additive, the catalyst metal is supported by the carrier, and the specific surface area of ​​the carrier is 600 m 2 / g-C or less, the conductive aid does not carry the catalyst metal and has an aspect ratio greater than that of the carrier, the aspect ratio of the conductive aid exceeds 10, when the total mass of the catalyst layer is 100 mass%, the proportion of the conductive aid included in the catalyst layer exceeds 2 mass% and is less than 20 mass%, and the conductive aid has not been hydrophilized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to catalyst layers. Background Art

[0002] A fuel cell (FC) is a power generation device that extracts electrical energy through an electrochemical reaction between a fuel gas such as hydrogen and an oxidant gas such as oxygen or air in a single cell or a fuel cell stack (hereinafter, simply referred to as a cell stack) formed by stacking multiple single cells (hereinafter, referred to as a unit). In addition, in the following, there are cases where fuel gas and oxidant gas are simply referred to as "reactant gas" or "gas" without making a special distinction.

[0003] The single cell of the fuel cell generally includes a membrane electrode assembly (MEA: Membrane Electrode Assembly).

[0004] The membrane electrode assembly has a structure in which a catalyst layer and a gas diffusion layer are sequentially formed on both sides of a solid polymer electrolyte membrane (hereinafter also referred to as "electrolyte membrane"). Therefore, the membrane electrode assembly is sometimes called a membrane electrode gas diffusion layer assembly (MEGA).

[0005] The single cell has two separators sandwiching the two sides of the membrane electrode gas diffusion layer assembly as needed. The separator usually has a structure in which a groove serving as a flow path for the reaction gas is formed on the surface in contact with the gas diffusion layer. In addition, the separator also functions as an electrical collector for power generation.

[0006] At the fuel electrode (anode) of the fuel cell, hydrogen (H2) as the fuel gas supplied from the gas flow path and the gas diffusion layer is protonated by the catalyst action of the catalyst layer, passes through the electrolyte membrane and moves to the oxidant electrode (cathode). At the same time, the generated electrons perform work through the external circuit and move to the cathode. Oxygen (O2) as the oxidant gas supplied to the cathode reacts with the protons and electrons on the cathode to generate water. The generated water gives the electrolyte membrane appropriate humidity, and the excess water passes through the gas diffusion layer and is discharged outside the system.

[0007] Various studies have been conducted on fuel cells that are mounted on fuel cell vehicles (hereinafter referred to as vehicles in some cases) for use.

[0008] For example, Patent Document 1 discloses a catalyst layer for a fuel cell in which conductive carbon fibers having a high aspect ratio are mixed.

[0009] Patent Document 2 discloses carbon fibers for a fuel cell including carbon particles and carbon nanofibers, wherein the carbon particles are agglomerated on the carbon nanofibers.

[0010] Patent document 3 discloses a fuel cell electrode catalyst in which a catalytic metal is supported on carbon containing at least one of nitrogen, phosphorus, oxygen and sulfur on the surface, carbon fiber with graphite C-face exposed on the surface, or a mixture of carbon and carbon fiber with graphite C-face ends exposed on the surface.

[0011] Patent Document 1: Japanese Patent Application Publication No. 2019-172476

[0012] Patent Document 2: International Publication No. 2017 / 135386

[0013] Patent Document 3: Japanese Patent Application Publication No. 2007-061698

[0014] As a power source for industrial vehicles represented by buses and trucks, the application of fuel cells has been attempted. These industrial vehicles are required to drive long distances, and the power performance is reduced due to oxidation degradation of the carbon carrier in the catalyst layer during long driving. As a countermeasure for oxidation degradation of the carbon carrier, the use of carbon raw materials with higher crystallinity is effective, but highly crystalline carbon has difficulty in forming a high-order structure between particles, and the specific surface area becomes smaller. In the case of forming a catalyst layer from carbon with a small specific surface area, the particles tend to be tightly packed together, making it difficult to form a high-order structure. Therefore, the catalyst layer is densified and the gas does not fully spread throughout the catalyst layer, and the initial power generation performance is reduced.

[0015] In order to prevent excessive densification, it is conceivable to mix a conductive agent having a predetermined aspect ratio or more with the catalyst layer. If the aspect ratio is too small or the amount of the conductive agent added is too small, the densification suppression effect cannot be obtained.

[0016] The conductive carbon fiber of the above-mentioned patent document 1 carries metal particles as a catalyst. The surface of the carbon carrying the metal particles is hydrophilized. In addition to the fact that the metal itself is hydrophilic, the carbon surface is hydrophilized without exception because it is usually subjected to an acid treatment process in the catalytic process. If a catalyst layer is formed from such hydrophilic carbon, the gas diffusion property is reduced due to the reduction in the drainage property of the catalyst layer, thereby reducing the power generation performance of the fuel cell. Summary of the invention

[0017] The present disclosure has been made in view of the above-mentioned actual situation, and a main object thereof is to provide a catalyst layer having low gas diffusion resistance and low proton resistance even when a carrier with a small specific surface area is used.

[0018] The catalyst layer disclosed in the present invention is a catalyst layer for a fuel cell, characterized in that the catalyst layer comprises a catalyst metal, a carrier and a conductive additive, the catalyst metal is supported by the carrier, and the specific surface area of ​​the carrier is 600 m 2 / gC or less, the conductive aid does not carry the catalyst metal and has an aspect ratio greater than that of the carrier, the aspect ratio of the conductive aid exceeds 10, and when the total mass of the catalyst layer is 100 mass%, the proportion of the conductive aid included in the catalyst layer exceeds 2 mass% and is less than 20 mass%, and the conductive aid has not been hydrophilized.

[0019] In the catalyst layer of the present disclosure, the conductive additive may have an aspect ratio of 18 to 40.

[0020] In the catalyst layer of the present disclosure, the catalyst layer may contain the conductive additive in a ratio of 7 mass % to 15 mass % when the total mass of the catalyst layer is 100 mass %.

[0021] In the catalyst layer disclosed herein, the support and the conductive additive may be carbon materials.

[0022] According to the catalyst layer of the present disclosure, even when a carrier having a small specific surface area is used, it is possible to reduce gas diffusion resistance and suppress an increase in proton resistance. DETAILED DESCRIPTION

[0023] The catalyst layer disclosed in the present invention is a catalyst layer for a fuel cell, characterized in that the catalyst layer comprises a catalyst metal, a carrier and a conductive additive, the catalyst metal is supported by the carrier, and the specific surface area of ​​the carrier is 600 m 2 / gC or less, the conductive aid does not carry the catalyst metal and has an aspect ratio greater than that of the carrier, the aspect ratio of the conductive aid exceeds 10, and when the total mass of the catalyst layer is 100 mass%, the proportion of the conductive aid included in the catalyst layer exceeds 2 mass% and is less than 20 mass%, and the conductive aid has not been hydrophilized.

[0024] In the present disclosure, a high aspect ratio conductive additive that does not support a catalyst metal is mixed with a carrier that supports a catalyst metal and has a small specific surface area, thereby forming a catalyst layer.

[0025] According to the present disclosure, the gas diffusion resistance can be reduced by the void formation effect and the hydrophobic effect. And by making the content of the conductive auxiliary agent within a specified range, the increase in proton resistance can be suppressed. As a result, by using the catalyst layer of the present disclosure in a fuel cell for an industrial vehicle that is driven for a long time, the initial power generation performance of the fuel cell can be improved, and the durability performance of the fuel cell can be improved.

[0026] The catalyst layer of the present disclosure includes a catalyst metal, a carrier, and a conductive additive. The catalyst layer may also include an electrolyte having proton conductivity as required.

[0027] The catalyst metal is supported on the carrier but is not supported on the conductive auxiliary agent.

[0028] As the catalyst metal, for example, platinum (Pt), an alloy composed of Pt and another metal (for example, a Pt alloy mixed with cobalt, nickel, etc.), or the like can be used.

[0029] The electrolyte may be a fluorine-based resin, etc. As the fluorine-based resin, for example, a perfluorosulfonic acid solution may be used.

[0030] The carrier may also be a carbon material. As the carbon material, for example, at least one selected from a group consisting of carbon black such as acetylene black and furnace black, vapor grown carbon fiber (VGCF), carbon nanotubes and carbon nanofibers may be cited, or carbon black may be used. For example, the carbon material may also be a hydrophobic carbon material having its own hydrophobicity improved by heat treatment.

[0031] The carrier supports the catalyst metal.

[0032] The specific surface area (SSA) of the carrier should be 600 m 2 / gC or less, or 580m 2 / gC or less. The specific surface area of ​​the carrier can also be 150m 2 / gC or more. If the specific surface area of ​​the carrier is 600m 2 / gC or less, the degradation of the carrier due to oxidation can be suppressed. If the specific surface area of ​​the carrier is 150m 2 / gC or more, it is easy to support the catalyst. It is considered that the same effect can be obtained as long as the specific surface area of ​​the carrier is within the range of measurement error of 5%.

[0033] The aspect ratio of the carrier is smaller than that of the conductive aid.

[0034] The shape of the carrier is not particularly limited as long as it satisfies the above-mentioned aspect ratio condition. Examples of the shape of the carrier include particle (sphere), scale, fiber, and irregular shape.

[0035] The conductive aid may also be a ceramic oxide, a carbon material, a metal material, etc. From the viewpoint of reducing gas diffusion resistance, the conductive aid may also be a carbon material. Examples of ceramic oxides include titanium oxide, etc. As a carbon material, for example, at least one selected from the group consisting of carbon black such as acetylene black and furnace black, vapor grown carbon fiber (VGCF), carbon nanotubes, and carbon nanofibers can be cited. In particular, from the viewpoint of electronic conductivity, at least one selected from the group consisting of VGCF, carbon nanotubes, and carbon nanofibers can be cited. As a metal material, Ni, Cu, Fe, SUS, etc. can be cited.

[0036] The conductive auxiliary agent does not support a catalyst metal.

[0037] The conductive aid has a larger aspect ratio than the carrier.

[0038] From the viewpoint of suppressing gas diffusion resistance, the aspect ratio (As) of the conductive auxiliary agent may exceed 10. The aspect ratio of the conductive auxiliary agent may be 18 or more and 40 or less.

[0039] The shape of the conductive additive is not particularly limited as long as it satisfies the above-mentioned aspect ratio condition. Examples of the shape of the conductive additive include particulate, flaky, fibrous, and irregular shapes, and may be flaky or fibrous.

[0040] The conductive aid uses a material that has not been subjected to a hydrophilic treatment. That is, the conductive aid has hydrophobicity. When the conductive aid is a carbon material, the carbon material in a state that has not been subjected to a hydrophilic treatment has hydrophobicity. The carbon material may also be a hydrophobic carbon material whose hydrophobicity has been improved by performing a heat treatment, for example.

[0041] The present disclosure is characterized in that a conductive auxiliary agent is kneaded into a catalyst-carrying carrier to form a catalyst layer, rather than catalyzing by carrying a catalyst metal on the conductive auxiliary agent. If the catalyst metal is carried on the conductive auxiliary agent, the surface of the conductive auxiliary agent is hydrophilized by the acid treatment usually performed in the catalytic process. Therefore, even in the case of a catalyst layer having a desired porosity, the drainage function is reduced, and the effect of reducing the gas diffusion resistance cannot be obtained.

[0042] According to the present disclosure, the porosity of the catalyst layer is increased by introducing the conductive auxiliary agent into the catalyst layer. In addition, since the conductive auxiliary agent is hydrophobic, water in the catalyst layer can be efficiently drained. Through these effects, the gas diffusivity of the catalyst layer is improved.

[0043] When the total mass of the catalyst layer is 100 mass %, the proportion of the conductive additive contained in the catalyst layer may be more than 2 mass % and less than 20 mass %, and may be 7 mass % to 15 mass %.

[0044] When the proportion of the conductive additive included in the catalyst layer exceeds 2 mass %, the effect of reducing gas diffusion resistance begins to be seen. When the proportion of the conductive additive included in the catalyst layer is less than 20 mass %, an increase in proton resistance can be suppressed.

[0045] The catalyst layer disclosed in the present invention is for use in fuel cells.

[0046] The fuel cell may include only one unit cell, or may be a fuel cell stack that is a stacked body in which a plurality of unit cells are stacked.

[0047] The number of stacked cells is not particularly limited, and may be, for example, 2 to several hundred, or 2 to 200.

[0048] The fuel cell stack may include end plates at both ends in the stacking direction of the single cells.

[0049] A single cell of a fuel cell includes at least a membrane electrode assembly.

[0050] The membrane electrode assembly includes an anode-side gas diffusion layer, an anode catalyst layer, an electrolyte membrane, a cathode catalyst layer, and a cathode-side gas diffusion layer in this order.

[0051] The cathode (oxidant electrode) includes a cathode catalyst layer and a cathode-side gas diffusion layer.

[0052] The anode (fuel electrode) includes an anode catalyst layer and an anode-side gas diffusion layer.

[0053] The cathode catalyst layer and the anode catalyst layer are collectively referred to as catalyst layers.

[0054] As the catalyst layer, the catalyst layer disclosed in the present invention is used.

[0055] The catalyst layer disclosed herein can be used as a cathode catalyst layer or as an anode catalyst layer. The catalyst layer disclosed herein can also be used at least as a cathode catalyst layer. The catalyst layer disclosed herein can also be used as a catalyst layer for both a cathode catalyst layer and an anode catalyst layer.

[0056] The cathode-side gas diffusion layer and the anode-side gas diffusion layer are collectively referred to as a gas diffusion layer.

[0057] The gas diffusion layer may be a gas-permeable conductive member or the like.

[0058] Examples of the conductive member include carbon porous bodies such as carbon cloth and carbon paper, and metal porous bodies such as metal mesh and foamed metal.

[0059] The electrolyte membrane may also be a solid polymer electrolyte membrane. As the solid polymer electrolyte membrane, for example, a fluorine electrolyte membrane such as a film of perfluorosulfonic acid containing water, and a hydrocarbon electrolyte membrane can be cited. As the electrolyte membrane, for example, a perfluorosulfonic acid membrane (manufactured by DuPont) may also be used.

[0060] The single cell may also include two separators sandwiching both sides of the membrane electrode assembly as needed. One of the two separators is an anode-side separator and the other is a cathode-side separator. In the present disclosure, the anode-side separator and the cathode-side separator are collectively referred to as separators.

[0061] The separator may also have a supply hole and a discharge hole for circulating the reaction gas and the refrigerant in the stacking direction of the single cell. As the refrigerant, in order to prevent freezing at low temperatures, for example, a mixed solution of ethylene glycol and water can be used. The reaction gas is a fuel gas or an oxidant gas. The fuel gas may also be hydrogen, etc. The oxidant gas may also be oxygen, air, dry air, etc.

[0062] Examples of the supply holes include a fuel gas supply hole, an oxidant gas supply hole, and a refrigerant supply hole.

[0063] Examples of the discharge hole include a fuel gas discharge hole, an oxidant gas discharge hole, and a refrigerant discharge hole.

[0064] The isolation member may have more than one fuel gas supply hole, may have more than one oxidant gas supply hole, may have more than one refrigerant supply hole, may have more than one fuel gas exhaust hole, may have more than one oxidant gas exhaust hole, and may have more than one refrigerant exhaust hole.

[0065] The separator may have a reaction gas flow path on the surface in contact with the gas diffusion layer. In addition, the separator may have a coolant flow path for maintaining a constant temperature of the fuel cell on the surface opposite to the surface in contact with the gas diffusion layer.

[0066] In the case where the separator is an anode side separator, it may have one or more fuel gas supply holes, one or more oxidant gas supply holes, one or more refrigerant supply holes, one or more fuel gas discharge holes, one or more oxidant gas discharge holes, and one or more refrigerant discharge holes. The anode side separator may have a fuel gas flow path on the surface in contact with the anode side gas diffusion layer for allowing the fuel gas to flow from the fuel gas supply hole to the fuel gas discharge hole, and may also have a refrigerant flow path on the surface opposite to the surface in contact with the anode side gas diffusion layer for allowing the refrigerant to flow from the refrigerant supply hole to the refrigerant discharge hole.

[0067] In the case where the separator is a cathode side separator, it may have more than one fuel gas supply hole, may have more than one oxidant gas supply hole, may have more than one refrigerant supply hole, may have more than one fuel gas discharge hole, may have more than one oxidant gas discharge hole, and may have more than one refrigerant discharge hole. The cathode side separator may have an oxidant gas flow path on the surface in contact with the cathode side gas diffusion layer for allowing the oxidant gas to flow from the oxidant gas supply hole to the oxidant gas discharge hole, and may also have a refrigerant flow path on the surface opposite to the surface in contact with the cathode side gas diffusion layer for allowing the refrigerant to flow from the refrigerant supply hole to the refrigerant discharge hole.

[0068] The separator may also be an airtight conductive component, etc. As the conductive component, for example, it may be a dense carbon compressed to be airtight, a stamped metal (for example, iron, aluminum, stainless steel, etc.) plate, etc. In addition, the separator may also have a current collecting function.

[0069] The fuel cell stack may include a manifold such as an inlet manifold through which the supply holes communicate and an outlet manifold through which the exhaust holes communicate.

[0070] Examples of the inlet manifold include an anode inlet manifold, a cathode inlet manifold, and a refrigerant inlet manifold.

[0071] Examples of the outlet manifold include an anode outlet manifold, a cathode outlet manifold, and a refrigerant outlet manifold.

[0072] [Example]

[0073] (Example 1)

[0074] A carrier on which a catalyst metal is supported (catalyst-supporting carrier) and a conductive auxiliary agent are prepared.

[0075] The specific surface area is 580m 2 / gC carbon material as a support.

[0076] Platinum was used as the catalyst metal.

[0077] Carbon fibers with an aspect ratio of 18 were used as conductive aids.

[0078] The catalyst-supporting carrier and the conductive additive are kneaded to prepare a catalyst layer.

[0079] The content of the conductive additive in the catalyst layer was 10% by mass.

[0080] The porosity of the catalyst layer was 30%.

[0081] The gas diffusion resistance was measured at a catalyst layer temperature of 60° C. and a relative humidity (RH) of 120%.

[0082] The proton resistance was measured at a catalyst layer temperature of 60° C. and a relative humidity of 30%.

[0083] The results are shown in Table 1.

[0084] (Example 2)

[0085] A catalyst layer was prepared in the same manner as in Example 1 except that carbon fibers having an aspect ratio of 40 were used as the conductive additive. The porosity, gas diffusion resistance, and proton resistance of the catalyst layer were measured.

[0086] The results are shown in Table 1.

[0087] (Example 3)

[0088] A catalyst layer was prepared in the same manner as in Example 1, except that the content of the conductive additive in the catalyst layer was 7% by mass. The porosity, gas diffusion resistance, and proton resistance of the catalyst layer were measured.

[0089] The results are shown in Table 1.

[0090] (Example 4)

[0091] A catalyst layer was prepared in the same manner as in Example 1 except that the content of the conductive additive in the catalyst layer was 15 mass %. The porosity, gas diffusion resistance, and proton resistance of the catalyst layer were measured.

[0092] The results are shown in Table 1.

[0093] (Comparative Example 1)

[0094] A catalyst layer was prepared in the same manner as in Example 1 except that carbon particles having an aspect ratio of 1 were used as the conductive auxiliary agent. The porosity, gas diffusion resistance, and proton resistance of the catalyst layer were measured.

[0095] The results are shown in Table 1.

[0096] (Comparative Example 2)

[0097] A catalyst layer was prepared in the same manner as in Example 1 except that carbon fibers having an aspect ratio of 10 were used as the conductive additive. The porosity, gas diffusion resistance, and proton resistance of the catalyst layer were measured.

[0098] The results are shown in Table 1.

[0099] (Comparative Example 3)

[0100] A catalyst layer was prepared in the same manner as in Example 1 except that no conductive auxiliary agent was used. The porosity, gas diffusion resistance, and proton resistance of the catalyst layer were measured.

[0101] The results are shown in Table 1.

[0102] (Comparative Example 4)

[0103] A catalyst layer was prepared in the same manner as in Example 1 except that the content of the conductive additive in the catalyst layer was 2 mass %. The porosity, gas diffusion resistance, and proton resistance of the catalyst layer were measured.

[0104] The results are shown in Table 1.

[0105] (Comparative Example 5)

[0106] A catalyst layer was prepared in the same manner as in Example 1 except that the content of the conductive additive in the catalyst layer was 20% by mass. The porosity, gas diffusion resistance, and proton resistance of the catalyst layer were measured.

[0107] The results are shown in Table 1.

[0108] (Comparative Example 6)

[0109] A catalyst layer was prepared in the same manner as in Example 1 except that the content of the conductive additive in the catalyst layer was 30% by mass. The porosity, gas diffusion resistance, and proton resistance of the catalyst layer were measured.

[0110] The results are shown in Table 1.

[0111] (Comparative Example 7)

[0112] A catalyst layer was prepared in the same manner as in Example 1 except that the conductive auxiliary agent hydrophilized by acid treatment was used. The porosity, gas diffusion resistance, and proton resistance of the catalyst layer were measured.

[0113] The results are shown in Table 1.

[0114] (Comparative Example 8)

[0115] In addition to using a specific surface area of ​​1200m 2 A catalyst layer was prepared in the same manner as in Example 1 except that a carbon material of 1000 Å / gC was used as a carrier and no conductive additive was used. The porosity, gas diffusion resistance, and proton resistance of the catalyst layer were measured.

[0116] The results are shown in Table 1.

[0117] (Comparative Example 9)

[0118] In addition to using a specific surface area of ​​1200m 2 A catalyst layer was prepared in the same manner as in Example 1 except that a carbon material of 1000 Å / gC was used as a carrier and the content of the conductive additive in the catalyst layer was 10 mass %. The porosity, gas diffusion resistance, and proton resistance of the catalyst layer were measured.

[0119] The results are shown in Table 1.

[0120]

Table 1

[0121]

Table 1

[0122]

[0123] The catalyst layer of Comparative Example 7 using the conductive auxiliary agent in a state of being hydrophilized by acid treatment can confirm an increase in porosity as in Example 1, but the effect of suppressing gas diffusion resistance is not large. It is believed that this is because the introduced conductive auxiliary agent is hydrophilic and therefore the drainage function in the catalyst layer cannot be fully obtained.

[0124] When using a specific surface area of ​​more than 600m 2 In the catalyst layer of Comparative Example 8 with a carrier of 1.5 Å / gC, the high-order structure is well developed, so the gas diffusion resistance is low even without the introduction of the conductive additive. It can be seen that in the catalyst layer of Comparative Example 9 in which the hydrophobic conductive additive is introduced into the catalyst layer of Comparative Example 8, the effect of increasing the porosity and reducing the gas diffusion resistance cannot be obtained.

[0125] Comparing the catalyst layers of Comparative Examples 1 and 2 and Examples 1 and 2, it can be seen that as the aspect ratio of the conductive agent increases, the porosity increases and the gas diffusion resistance decreases. In addition, it can be seen that the increase in proton resistance can be suppressed by the aspect ratio of the conductive agent exceeding 10 and being 40 or less.

[0126] When the catalyst layers of Comparative Examples 3 to 6 and Examples 3 to 4 are compared, the porosity increases as the content of the conductive aid in the catalyst layer increases. It can be seen that when the content of the conductive aid in the catalyst layer is 20% by mass or more, the gas diffusion resistance can be reduced, but the proton resistance increases. Therefore, it can be seen that when the content of the conductive aid in the catalyst layer exceeds 2% by mass and is less than 20% by mass, the balance between the gas diffusion resistance and the proton resistance is excellent.

Claims

1. A catalyst layer for a fuel cell, characterized in that: The catalyst layer includes a catalyst metal, a carrier and a conductive additive. The catalyst metal is supported by the carrier, and the specific surface area of ​​the carrier is 580 m 2 / gC, The conductive auxiliary agent does not support the catalyst metal and has an aspect ratio greater than that of the carrier, The conductive additive has an aspect ratio of 40, When the total mass of the catalyst layer is 100 mass %, the proportion of the conductive additive included in the catalyst layer is 10 mass %, The conductive auxiliary agent is not subjected to hydrophilization treatment.

2. The catalyst layer according to claim 1, characterized in that The carrier and the conductive aid are carbon materials.

Citation Information

Patent Citations

  • Electrode catalyst for fuel cell, membrane electrode assembly, fuel cell and portable electronic equipment

    JP2007061698A

  • Conductive nanofiber member, member for fuel cell, fuel cell, and method for producing conductive nanofiber member

    JP2019172476A

  • Carbon-based catalyst comprising composite material

    WO2017135386A1

  • Process for producing membrane / electrode assembly for polymer electrolyte fuel cell

    CN104022300A

  • Catalyst composition for cell, gas diffusion layer, and fuel cell comprising the same

    US20030091891A1